Effect of phosphoric acid-doped polybenzimidazole membranes on the performance of H+-ion concentration cell. (19th January 2021) - Qu, Ting; Hu, Jixiang; Tan, Qiang; Liu, Yan; Chen, Yuanzhen; Sun, Junjie; Liu, Yongning
Abstract: H + -ion concentration cell, which can harvest thermal energy to generate electricity by hydrogen concentration difference principle with a fuel cell structure, is an innovative thermoelectric conversion device. In this system, phosphoric acid-doped polybenzimidazole (PA-doped PBI) membrane is a key component influencing the power generation performance of the cell. Herein, 30, 45, 60, 75, and 90 μm thick PBI membranes are successfully synthesized and doped with phosphoric acid. To achieve a good compromise between the proton conductivity and durability, the properties of PA-doped PBI membranes are experimentally evaluated to clarify the effect of the acid doping time and membrane thickness on cell performance. The results indicate that the higher the acid doping level, the worse the dimensional stability of the membrane. Also the thinner the PBI membrane, the smaller the membrane resistance to ions motion, while the poorer the stability. Upon reaction at 170 °C, this cell can boast a power density from 3.0 to 8.0 W m −2, which results in a thermoelectric conversion efficiency of 5.97–14.32%. This study potentially boosts the practical application of thermal-to-electrical conversion technology. Graphical abstract: Image 1 Highlights: The properties of different PBI membranes were studied. Phosphoric acid-doped PBI membranes exhibited good proton conductivity and thermal stability. The H + -ion concentration cell can boast a power density from 3.0 to 8.0 W m −2 at 170 °C. The thermoelectric conversion efficiency across the H + -ion concentration cell is in the range of 5.97–14.32%.